TEACHERS’ INSTRUCTIONAL EFFECTIVENESS IN BIOLOGY IN OBINGWA LOCAL GOVERNMENT AREA, ABIA STATE (UNIZIK Journal of STM Education, 2025)
This study was designed to determine the effect of the use of Internet on teachers’ instructional effectiveness in Biology. Pre and post non-control design was used for the study. Two research questions and two hypotheses guided the study. The population of the study consisted of 32 SS11 Biology teachers in Obingwa Local Government Area, Abia state Nigeria. A sample of twelve teachers, six males and six females gotten through multi-stage sampling technique were used for the study. The instrument used for data collection was Teachers’ Instructional Effectiveness Scale (TIES) with internal consistency of 0.90 established using Cronbach alpha approach. Mean and standard deviation were used to answer the research questions. Hypotheses one and two were tested using the paired sample t-test and Analysis of Covariance respectively at 0.05 level of significance. The result revealed that the use of Internet in teaching enhances teachers’ instructional effectiveness. More so, there was no significant difference between the male and female teachers’ instructional effectiveness. It was therefore recommended that Biology teachers should use Internet in planning and delivering of lessons for improved instructional effectiveness.
Keywords: Internet, Biology, Instructional effectiveness